HOW TO IMPROVE INTERNAL AUDIT QUALITY IN NORTH SUMATERA GOVERNMENT: THE EFFECT OF TIME BUDGET PRESSURE - Muhammad Irsan Nasution; Erlina; Iskandar Muda; Zulkarnain (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
The primary objective of this study is to examine the various determinants that influence time budget pressure within the context of the regional government of North Sumatra province. Furthermore, this research aims to assess the subsequent effects of such pressure on the overall quality of internal audits conducted within the regional government of North Sumatra province. The influencing factors encompass job completion time, continuous audit assignments, and involvement in arranging audit time. The research data was acquired by distributing questionnaires to respondents who were auditors working at provincial and district/ city inspectorates in the region of North Sumatra. The multiple regression data analysis comprised 130 questionnaires deemed usable for the study. This study offers significant insights for inspectorates and provincial and district/ city governments in North Sumatra to effectively identify the determinants of time budget pressure and its subsequent effects on the quality of internal audits. The individual demonstrates a high level of professionalism and adherence to ethical standards. One of the primary challenges currently confronting auditors is the imperative to broaden their audit methodologies and establish comprehensive standards that effectively oversee the activities of corporate organizations. The current prevalence of high turnover rates serves as a poignant reminder to organizations invested in training and providing adequate resources to address the challenges auditors encounter in their professional environments. This study examines the various elements that contribute to time budget pressure and its subsequent effects on the quality of internal audits within the regional administration of North Sumatra province.